EVALUATING OF INDIRECT SOLAR DRYER EFFICIENT PERFORMANCE AND IT'S IMPACT ON SOME MEDICAL PLANTS ACTIVITY - & Almaaeny, Jebur (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
The solar dryer is designed and manufactured to dry some medical plants at the  Research Center for Energy and Environment of the Ministry of Industry and Minerals. this experiment was included two factors, where three levels speeds for the fan were selected (0.101, 0.065, 0.056 m3/s)  which represented the main factor  and  three kind of medical plants ,( mint, pepper and ginger).factorial experiment within  Complete Randomized Design with three replications  was used to study the effect of the dried substance type ,air flow rate and their overlap with  studied parameters. The results indicated that when the air flow rate increased, daily theoretical efficiency increased by 6.74%. and the theoretical and practical efficiency increases as you say the intensity of the fallen solar radiation. The increased intensity of the fallen solar radiation is resulting in a lower efficiency of the solar dryer. The alcohol extract of ginger was more effective against the growth of E.Coli bacteria than the rest of the extracts where the diameters ranged 20-25 mm. The alcohol extract of the pepper was effective against the growth of the Staphy.aureus bacteria better than the rest of the extracts where the diameters ranged (11-17) mm.